Large Scale Land Acquisitions and Land Governance in Uganda: Implications for Women’s Land Rights - Ahikire, Josephine; Nassali, Maria; Kanyesigye, Juliet; Nakayi, Rose; Pamara, Harriet; Katushabe, Jovah (International development Research Centre, 2016)
Over 90 percent of Uganda’s population is dependent almost exclusively on agriculture for their livelihood which makes land a vital resource and in the same vein land governance then becomes a significant political question. Over the last two decades or so, there has been a relative land rush by foreign companies as well as national companies and individual investors and speculators. The phenomenon of LSLA in Uganda is quietly on the rise.